POLYOSTOTIC FIBROUS DYSPLASIA: RESPONSE TO ZOLENDRONIC ACID - Ong, Jia Cheng; Samsudin, Ahmad Hadif Zaidin; Hussain, Suhaimi (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Fibrous Dysplasia is a rare developmental bone disorder in which fibro-osseous tissue replaces normal bone tissue. It can manifest either monostotic or polyostotic associated with McCune-Albright syndrome. Bisphosphonates such as pamidronate and alendronate have been used to improve bone mineral density due to antiresorptive properties. However, the literature on the use of zoledronate is limited. CASE A 10-year-old female presented with a fracture of the right midshaft of the femur following a trivial fall. She had a history of precocious puberty and limping gait since the age of four years old. On examination, she was tall for her age and there was thoracolumbar scoliosis with huge cafe au lait patches at her lower back. Biochemically, she had elevated alkaline phosphatase level and low serum vitamin D. Skeletal survey revealed multiple patchy areas of lucency with irregular margins in the long bones, skull and pelvis. Bone mineral density was low suggestive of osteoporosis. Her fracture of the right midshaft of the femur was due to polyostotic fibrous dysplasia with underlying McCuneAlbright syndrome. As bisphosphonate is required in fibrous dysplasia, she was treated with multiple doses of intravenous zoledronate starting at 0.0125 mg per kg which she tolerated well and then increased to 0.025 mg per kg. Her response was good, evidenced by reduced alkaline phosphatase level and improved bone mineral density. Her fracture healed with no complications or incidence of new fracture. CONCLUSION The administration of intravenous zoledronate enhances bone mineral density and demonstrates improvements in bone biomarkers. It was well tolerated and should be used in McCune-Albright syndrome with fibrous dysplasia of the bone.